Identifying the involvement of multiple carnivore taxa with archaeological bone assemblages - Selvaggio, Marie M; Wilder, Joseph (Journal of Archaeological Science, 2001)
Information on the number of carnivore taxa that were involved with archaeological bone assemblages is pertinent to questions of site formation, hominid and carnivore competition for carcasses and the sequence of hominid and carnivore activity at sites. A majority of early archaeological bone assemblages bear evidence that both hominids and carnivores removed flesh and/or marrow from the bones. Whether flesh specialists (felids) or bone-crunchers (hyaenas), or both, fed upon the carcasses is crucial for deciphering the timing of hominid involvement with the assemblages. Here we present an initial attempt to differentiate the tooth mark signature inflicted on bones by a single carnivore species versus multiple carnivore taxa. Quantitative data on carnivore tooth pits, those resembling a tooth crown or a cusp, are presented for two characteristics: the area of the marks in millimetres, and the shape as determined by the ratio of the major axis to the minor axis of the mark. Tooth pits from bones modified by extant East African carnivores and latex impressions of tooth pits from extinct carnivore species are compared to those in the FLK Zinjanthropus bone assemblage. Data on tooth mark shape indicate greater variability in the Zinj sample than is exhibited by any individual extant or extinct carnivore species in the comparative sample. Data on tooth mark area demonstrate that bone density is related to the size of marks. Taken together, these data support the inference that felids defleshed bones in the Zinj assemblage and that hyaenas had final access to any grease or tissues that remained. © 2001 Academic Press.
Keywords: Carnivore tooth marks; Methodology; Site formation; Taphonomy; carnivore; dept.ant; dept.soc; feeding; taphonomy; tooth